Household garbage classification based on deep learning - Wang, Yong (Nanyang Technological University, 2022)
Garbage classification plays an essential role in protecting the earth’s ecological environment and promoting economic development. Before computer vision technology was developed, waste classification was mostly carried out by manual sorting, which has some disadvantages such as high labor intensity, low sorting efficiency, and poor working environment.